Integrasi Nilai Budaya Lokal Banjar dalam Edukasi Pencegahan Stunting bagi Ibu Balita di Wilayah Kerja Puskesmas Martapura 1 - Filia Sofiani Ikasari; Iis Pusparina (Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting remains a public health problem with long-term impacts on the quality of human resources; therefore, contextual and socially acceptable prevention efforts are needed. This topic was selected due to the limited understanding of mothers of toddlers regarding stunting prevention and the suboptimal use of local cultural values as a medium for health education. This community service activity aimed to improve mothers’ knowledge about stunting prevention through the integration of Banjar local cultural values. The community service method applied participatory community education conducted at Posyandu ILP Subur, Jawa Laut Village, utilizing stunting prevention posters in the Banjar language and baimbai bapandir group discussions. The results showed an increase in participants’ knowledge, from 60% in the good category at the pre-test to 100% in the good category at the post-test. It can be concluded that Banjar culture-based stunting prevention education is effective in improving mothers’ knowledge and has the potential to be replicated in other areas.